The Relationship between Health Service Quality, Servicescape, and Socio-demographic Factors on Outpatient Satisfaction Levels at Clinic X - Vicko Pratama; Innocentius Bernarto (Budapest International Research and Critics University, 2022)
The objectives of this study were to analyze the positive association between qualities of health services towards patient satisfaction, analyze the positive association between servicescape towards patient satisfaction, and analyze the association between socio-demographic factors towards patient satisfaction. In this study, data were collected using a questionnaire. All patients visiting in the outpatient of X Clinic were recruited between July until August 2021, and 160 respondents were obtained using the convenience sampling method. Data were analyzed for descriptive and inferential statistics using the SMARTPLS program. Results of the data analysis showed that there was a significant positive association between quality of health services towards patient satisfaction, a significant positive association between servicescape towards patient satisfaction, and a significant association between socio-demographic factors towards patient satisfaction. These findings implicated the need to improve the quality of health services, servicescape, and socio-demographic factors in the clinical managerial process.